Expression of transforming growth factor beta 1-related signaling proteins in irradiated vessels - Preidl, Raimund; Moebius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Wehrhan, Falk (Strahlentherapie und Onkologie, 2015)
Microvascular free tissue transfer is a standard method in head and neck reconstructive surgery. However, previous radiotherapy of the operative region is associated with an increased incidence in postoperative flap-related complications and complete flap loss. As transforming growth factor beta (TGF-?) 1 and galectin-3 are well known markers in the context of fibrosis and lectin-like oxidized low-density lipoprotein 1 (LOX-1) supports vascular atherosclerosis, the aim of this study was to evaluate the expression of TGF-?1 and related markers as well as LOX-1 in irradiated vessels.To evaluate the expression of galectin-3, Smad 2/3, TGF-?1, and LOX-1, 20 irradiated and 20 nonirradiated arterial vessels were used for immunohistochemical staining. We semiquantitatively assessed the ratio of stained cells/total number of cells (labeling index).Expression of galectin-3, Smad 2/3, and TGF-?1 was significantly increased in previously irradiated vessels compared with nonirradiated controls. Furthermore, LOX-1 was expressed significantly higher in irradiated compared with nonirradiated vessels.Fibrosis-related proteins like galectin-3, Smad 2/3, and TGF-?1 are upregulated after radiotherapy and support histopathological changes leading to vasculopathy of the irradiated vessels. Furthermore, postoperative complications in irradiated patients can be explained by increased endothelial dysfunction caused by LOX-1 in previously irradiated patients. Consequently, not only TGF-?1 but also galectin-3inhibitors may decrease complications after microsurgical tissue transfer.
EVALuna2:24387